La poésie dans l'apprentissage du roumain langue étrangere - Jieanu, Ioana (Vestnik za tuje jezike, 2014)
Our research elaborates upon the possible effects of using poetry in the process of learning the Romanian language: cultural awareness, and developing a sense of language, as well as observation and comparison of poetic language. For this purpose, we analyze how poetry and the poetic language were introduced in the Romanian language course. A total of 12 students participated in our research, all of whom speak at least four foreign languages, including two Romance languages. The Romanian poetic language acquired during poem reading or song listening was reconsidered in follow-up creative writing activities, either individual (the picture poems, the symbolist poetry, the acrostic) or collective (the Dadaist poetry).
Keywords: romunščina; tuji jeziki; didaktika jezika; pesniški jezik; kaligrami; dadaistična poezija